Review on Admixture for Civil Engineer - Patil, Somraj S.; Khochare, Rajvardhan N.; Gondil, Rajvardhan P.; Maske, Mayur M. (Universitas Pendidikan Indonesia (UPI), 2021)
The purpose of this study was to report a review on admixture. This review is important for giving ideas and knowledge about admixture, from the definition to the practical application, to practitioners in the civil engineering field. In short, water-reducing and set-controlling admixtures have proven themselves to be useful tools in the precast industry. They can significantly reduce the water-cement ratio (w/c), decreasing the use of cement, altering the set time to help in production, improving workability, and decreasing permeability. Their use does not, however, preclude the use of good concrete practices such as curing. The type of admixture and dosage recommended varies depending on manufacturers, and it must be considered with other materials. We also discussed the specific operations with the admixture supplier to ensure that the process can be done in the most economical condition.